The Chinese Medical Doctor Association: A New Industrial Relations Actor in China’s Health Services? - Cao, Xuebing (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2011)
This research marks a new attempt to examine the development of new industrial relations actors in contemporary China. It appears that the CMDA has the potential to convert members’ common pursuit into action, albeit with different strengths and patterns compared with its Western counterparts. However, the process of mobilizing doctors is likely to be challenged by China’s unitary industrial relations system. For Chinese doctors, the question is how to convert constant work-related discontent and conflict into an institutional response, and how much freedom the CMDA can be given. Follow-up observation is needed to assess the impact of the CMDA’s continuous expansion in the industrial relations system in China’s health services.Findings suggest that currently the CMDA is neither an independent union organization, nor a new industrial relations actor within Chinese health services due to its structural weakness and political limitations. Unlike its Western counterparts, the CMDA does not have high levels of social and economic power to control licenses and access to the medical profession. However, the prospect remains that the CMDA may be more active within the industrial relations system if doctors’ social capital and group identity can be further strengthened.This paper examines possibilities and difficulties for the Chinese Medical Doctor Association (CMDA) to become a new industrial relations actor in China’s health services. It attempts to provide evidence on whether the CMDA functions in similar ways as its Western counterparts in mobilizing members. Aiming at filling the research gap in Chinese professional organizations’ involvement in the industrial relations process, this paper discusses the CMDA’s potential and the challenges of becoming a union organization. Data were collected through 39 semi-structured interviews with supplementation of documentary evidence from the government, doctors’ professional societies, hospitals and trade unions.